Pengaruh Lingkungan Pembelajaran Terhadap Prestasi Belajar Siswa Pada Mata Pelajaran Fiqih Di Ma Unggulan - Setia budi, Ryan; Badriyah, Laila (Universitas Majalengka, 2023)
This research determines the influence of the learning environment at school on student learning achievement in fiqh subjects at MA Unggulan Tlasih Tulangan Sidoarjo. This type of research is quantitative descriptive. The student population in this study was students from class Meanwhile, data analysis techniques use percentages and product moments. Based on the percentage analysis that the Influence of the Learning Environment at Ma Unggulan Tlasih Tulangan Sidoarjo shows a result of 63.19%, then fulfilling the interval of 61%-80% can be categorized as Good. The Product Moment Correlation obtained by rxy 0.550 is greater than the r table 0.209, namely 0.550 > 0.209. That there is an influence of the Learning Environment on Student Learning Achievement. This is evident from the r value coefficient interpretation table that the rxy value of 0.550 is between the values 0.40 – 0.599 which is categorized as Medium, so it can be concluded that Ho is rejected and Ha is accepted, which means that there is an influence of the learning environment at school on learning achievement at the Leading MA Tlasih Tulangan Sidoarjo.